Biomassa Dan Cadangan Karbon Di Kawasan Agroforestri Karet Tradisional Di Desa Nanga Pemubuh Kecamatan Sekadau Hulu Kabupaten Sekadau - Riza Linda, Alinus, Rafdinal, (Jurnal Protobiont, 2017)
Carbon stock is carbon content strored either on the ground surface serving as plant biomass or in the ground functioning as soil organic matter. One of the area which can potentially absorb a large amount of carbon is traditional rubber agroforestry. This research aims at identifying biomass an carbon stock stored in the research site. The research was conducted for three mounths, starting from March to July 2017 in Nanga Pemubuh village. The identification of plant types was carried out in the biology lab of Mathematic and Natural Science Faculty, Tanjungpura University. To measure biomass and carbon stock, the research employed a transect method on tree stands with diameters more than 25 cm. Results revealed that the rate of density obtained in this research was about 6.5-46 trees/ha. After that, the biomass gathered was about 42.79 - 222.43 ton/ha and the stock ranged around 21.39 - 111.22 ton/ha.